Transfer of Japanese Culture Patterns on the Example of a Comic Book: How Manga Conquered the World and Became an Integral Part of the Polish Publishing Market? - Bazylewicz, Tomasz (Studia Historiae Oeconomicae, 2018)
Transfer of Japanese Culture Patterns on the Example of a Comic Book. How Manga Conquered the World and Became an Integral Part of the Polish Publishing Market?